2019
DOI: 10.3389/fpsyg.2019.02549
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Dual Filial Piety and Life Satisfaction: The Mediating Roles of Individuating Autonomy and Relating Autonomy

Abstract: Filial piety (FP) was formerly a Confucian concept that specifies how children should treat their elders. In recent years, some psychologists have postulated that there are considerable overlaps between Chinese FP and notions found in other cultures. They have redefined FP as a contextualized personality emphasizing the psychological schema of parent-child interaction so that it fits universal cultural contexts. Based on this theory construction, this study aimed to examine the effects of reciprocal FP and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
2
36
0
1
Order By: Relevance
“…A recent study demonstrated that although AFP has a negative indirect effect on life satisfaction through the mediating role of individuating autonomy, it has a positive indirect effect through relating autonomy (Sun et al, 2019). An additional benefit of the DFPM is that rather than simply designating people as filial or un-filial, the model allows for a more nuanced examination of the psychological mechanisms underlying the affective reactions and social behavior associated with filial piety by identifying four possible modes of personal interaction with parents: high reciprocal-low authoritarian, high authoritarian-low reciprocal, high on both (balanced), and low on both (non-filial) (Yeh and Bedford, 2004).…”
Section: Psychosocial Adjustment: Individual Level Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that although AFP has a negative indirect effect on life satisfaction through the mediating role of individuating autonomy, it has a positive indirect effect through relating autonomy (Sun et al, 2019). An additional benefit of the DFPM is that rather than simply designating people as filial or un-filial, the model allows for a more nuanced examination of the psychological mechanisms underlying the affective reactions and social behavior associated with filial piety by identifying four possible modes of personal interaction with parents: high reciprocal-low authoritarian, high authoritarian-low reciprocal, high on both (balanced), and low on both (non-filial) (Yeh and Bedford, 2004).…”
Section: Psychosocial Adjustment: Individual Level Of Analysismentioning
confidence: 99%
“…A number of studies have applied a measure based on the DFPM, the dual filial piety scale (DFPS; Yeh and Bedford, 2003 ) to examine the authoritarian and reciprocal filial motivations in relation to various aspects of the psychosocial adjustment of adolescents. For example, RFP is positively correlated with life satisfaction ( Wong et al, 2010 ; Sun et al, 2019 ) as well as good interpersonal skills (e.g., self-disclosure and empathy), reduced parent-child conflict ( Yeh and Bedford, 2004 ), and better overall psychosocial adjustment ( Yeh and Yang, 2006 ). RFP mediates the influence of supportive parenting on young adults’ happiness ( Chen et al, 2016 ).…”
Section: Application Of the Dfpm And Integration With Research In Other Societiesmentioning
confidence: 99%
See 1 more Smart Citation
“…RFP is associated with other strategies for handling conflict with parents that allow adolescents to both fulfill parental expectations and achieve personal goals. In addition, previous research has indicated that those who endorse RFP may not only maintain harmonious interaction with their parents (Li et al, 2014;Chen et al, 2016), but also acquire strong individuating autonomy (Sun et al, 2019). Existing evidence also supports the association of the compatibility and compromise strategies with better adaptation in the parent-child relationship and in personal life (Yeh and Tsao, 2014;Wu et al, 2019).…”
Section: Resolution Strategies In Line With Filial Pietymentioning
confidence: 92%
“…Отечественные и зарубежные исследователи (Утюганов, Яницкий и Серый, 2019;Алексеева, 1984;Ермак, 2016;Барадакова, 2017;Волынец, 2017;Зубова и Кириенко, 2018;Калугин, 2017;Колесов, Смолонская и Смолонский, 2017;Лифшиц, 2019;Лобза, Конончук и Эгамбердиева, 2017;Бутакова и Вязигина, 2017;Damasio & Koller, 2015;Datu, 2016;Donina, Salikhova, Aryabkina, Chernova, & Kovardakova, 2019;Knyazeva et al, 2019;Litvinova & Kolomoichuk, 2016;Park & Baumeister, 2017;Sun, Fan, Sun, Jiang, & Wang, 2019; и др.) продолжают изучать ценности, входящие в структуру личности.…”
unclassified